IMAGE-BASED 3D RECONSTRUCTION DATA AS AN ANALYSIS AND DOCUMENTATION TOOL FOR ARCHITECTS: THE CASE OF PLAKA BRIDGE IN GREECE - T. Kouimtzoglou (National Technical University of Athens, School of Architecture, Dep. IV Architectural Technology Patision 42 st., 10682, Athens, Greece) (Copernicus Publications, 2018)
Μodern advances in the field of image-based 3D reconstruction of complex architectures are valuable tools that may offer the researchers great possibilities integrating the use of such procedures in their studies. In the same way that photogrammetry was a well-known useful tool among the cultural heritage community for years, the state of the art reconstruction techniques generate complete and easy to use 3D data, thus enabling engineers, architects and other cultural heritage experts to approach their case studies in an exhaustive and efficient way. The generated data can be a valuable and accurate basis upon which further plans and studies will be drafted. These and other aspects of the use of image-based 3D data for architectural studies are to be presented and analysed in this paper, based on the experience gained from a specific case study, the Plaka Bridge. This historic structure is of particular interest, as it was recently lost due to extreme weather conditions and serves as a strong proof that preventive actions are of utmost importance in order to preserve our common past.